Approach to Lipid Screening as a Risk Marker for Cardiovascular Disease in Pediatric Patients with Diabetes - Law, Jennifer R.; Patel, Shipra; Spagnoli, Anna (Frontiers in Endocrinology, 2011)
Cardiovascular disease (CVD) is a well-known complication of diabetes mellitus (DM), and patients with DM are at an increased risk for early onset of CVD. Hyperglycemia is believed to be the primary mediator in premature development of atherosclerosis in patients with DM, but there are also derangements in cholesterol levels and inflammatory markers beyond the explanation of hyperglycemia. Although clinicians often screen for dyslipidemia as part of routine care for children and adolescents with DM, many do not feel comfortable treating this condition. Multiple guidelines exist to help clinicians with the prevention, screening, and treatment of CVD risk factors in pediatric patients with DM, but the guidelines do not always agree on screening intervals or medical treatment. Furthermore, the cost-effectiveness of medication use in this population has not been established. Research has advanced our understanding of the role of other biomarkers and radiologic studies of CVD risk, but these studies do not currently have a place in routine clinical practice. It is evident that the increased CVD risk in pediatric patients with DM is complex in origin and the optimal approach to managing dyslipidemia remains unclear. Therefore, an algorithm designed at the University of North Carolina, Division of Pediatric Endocrinology, is presented to help guide clinicians through screening and treatment of dyslipidemia in youth with DM.